2012
DOI: 10.4028/www.scientific.net/amr.460.342
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Modeling for Prediction of Thermal Conductivity of Plain Weave C/SiC Composites Considering Manufacturing Flaws

Abstract: Utilized photomicrographs taken by scanning electron microscope (SEM), an accurate representative volume element (RVE) model for plain weave C/SiC composites is established. Based on the steady-analysis method, the in-plane and thickness direction thermal conductivity of the C/SiC composites are calculated as 25.6Wm-1K-1 and 12.1Wm-1K-1, respectively. The manufacturing flaws have different effect on thermal conductivity. Compared with RVE without flaws, the result shows that matrix cracks make thermal conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Two‐dimensional C/SiC composites have attracted increasing interests in recent years due to their low densities, high specific strengths, 1 elevated specific module, 2 and noncatastrophic mode of failure, 3 which made them promising thermal structural materials for applications in aerospace, aircraft braking, and space detection 1,4,5 . However, these harsh environments require them possessing not only thermal structural performances like load resistance, 2 but also functional properties such as high thermal conductivity, especially in thickness direction of the composites (about 5‐12 W·m −1 ·K −1 for now) 6‐9 . Therefore, C/SiC composites cannot serve as a functional materials for aerospace vehicle thermal discharge and active cooling of ramjet combustion chamber but a thermal structural materials.…”
Section: Introductionmentioning
confidence: 99%
“…Two‐dimensional C/SiC composites have attracted increasing interests in recent years due to their low densities, high specific strengths, 1 elevated specific module, 2 and noncatastrophic mode of failure, 3 which made them promising thermal structural materials for applications in aerospace, aircraft braking, and space detection 1,4,5 . However, these harsh environments require them possessing not only thermal structural performances like load resistance, 2 but also functional properties such as high thermal conductivity, especially in thickness direction of the composites (about 5‐12 W·m −1 ·K −1 for now) 6‐9 . Therefore, C/SiC composites cannot serve as a functional materials for aerospace vehicle thermal discharge and active cooling of ramjet combustion chamber but a thermal structural materials.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal conductivity 𝜆 is essential for evaluating the heat transfer performance of composites. [19,20] Many works have been conducted to predict the anisotropic thermal conductivity 𝜆anisotropic of C/SiC composites numerically, [21][22][23][24] and yet the corresponding experimental studies at high temperature are rarely reported. For the studies of the measurement of the 𝜆 out-of-plane , Zhang et al [11,12] obtained the out-of-plane thermal diffusivity 𝑎 out-of-plane of 2D plain woven C/SiC composite using a laser flash analysis (LFA) method within the temperature range of 100-500 ∘ C. Cai et al [13] measured the 𝑎 out-of-plane of 3D C/SiC composite over a temperature range from 25 ∘ C to 1300 ∘ C by adopting the LFA method, and the 𝜆 out-of-plane was obtained by measuring its specific heat capacity and density simultaneously.…”
mentioning
confidence: 99%